2023
DOI: 10.3390/futuretransp3040068
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Barriers and Expectations in MaaS: Users’ and Stakeholders’ Perspective

Andreas Nikiforiadis,
Despoina Tsavdari,
Vasilis Mizaras
et al.

Abstract: Mobility as a Service (MaaS) is an innovative urban mobility concept that aims to provide a competitive alternative to the use of private cars, by integrating various transportation services. Until today, limited MaaS schemes have been implemented and, in most cases, without succeeding to justify the hype. For achieving the goals of MaaS it is essential to capture holistically the expectations and barriers, as perceived by both the end-users and the various involved stakeholders. This paper aims to bridge this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Multiple mobility companies have collaborated to develop a comprehensive MaaS system with only electric vehicles [e-MaaS], as a one-stop-shop for mobility, that will provide functionality to travellers. Research that was conducted showed that users are particularly concerned with protection of personal data and security of transactions, while young people [18,[24][25][26][27][28][29] and frequent PT passengers are the most willing to use the scheme [30]. The present study utilizes a triangulation approach, by combining quantitative and qualitative analysis, in order to enhance validity and credibility of the results, provide a comprehensive understanding of the opportunities and the challenges around MaaS schemes, and mitigate potential bias.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mobility companies have collaborated to develop a comprehensive MaaS system with only electric vehicles [e-MaaS], as a one-stop-shop for mobility, that will provide functionality to travellers. Research that was conducted showed that users are particularly concerned with protection of personal data and security of transactions, while young people [18,[24][25][26][27][28][29] and frequent PT passengers are the most willing to use the scheme [30]. The present study utilizes a triangulation approach, by combining quantitative and qualitative analysis, in order to enhance validity and credibility of the results, provide a comprehensive understanding of the opportunities and the challenges around MaaS schemes, and mitigate potential bias.…”
Section: Introductionmentioning
confidence: 99%